Incident Factors in the Sustainable Development of Digital Teaching Competence in Dual Vocational Education and Training Teachers - Jesús Sánchez-Prieto; Juan Manuel Trujillo-Torres; Melchor Gómez-García; Gerardo Gómez-García (MDPI AG, 2021)
For years the technological revolution has been transforming all facets of our society. Teaching could obviously not be an exception but is quite the opposite because of its role in training the individuals of that society. Teachers at all levels of education are subjected to an adaptation process to develop the digital skills necessary for this transformation. This process must be permanent as there are still major deficiencies in teachers' ICT knowledge and rejection of their application. This study aims to see whether the inadequacy of digital teaching skills also occurs in the Dual Vocational Training modality. To this end, a descriptive quantitative method has been carried out in a sample of teachers from the Professional Formation Dual system in the Autonomous Community of Andalusia. The results show an insufficient level of digital skills that is therefore improvable, finding some factors that influence, to some extent, the various components of digital competence such as prior teacher training, the locality in which their school resides or the category of teaching to which he belongs. Therefore, it is advised to continue to promote in-service training in digital competence for in-service teachers in order to achieve sustainable educational development.